Evaluating Information Literacy Competence in the Use of Electronic Resources among Medical Students in University of Ilorin, Nigeria - Bashorun, Musediq Tunji; Bashorun, Rafiat Bukola; Akinbowale, Aishat Temitope (University of Dar es Salaam Library Journal, 2021)
University library orgarnised information literacy programme to enable undergraduates acquire and used Electronic Resources (ERs) with huge amount of money to satisfy users. This is aimed at addressing low utilization of ERs by undergraduates. In view of the programme, this study attempted to investigate the information literacy competence on the use of ERs by medical students in the Faculty of Clinical Sciences, University of Ilorin, Nigeria. The study adopted a descriptive survey design. 260 of undergraduates in the Faculty of Clinical Sciences were randomly selected out of the study ' s population of 771. Data were collected using questionnaire designed to elicit response from respondents and data were analysed using the Statistical Package for Social Sciences (IBM-SPSS) version 21.0 with descriptive statistics methods percentages, frequency, analysis of variance and correlation analysis. The findings revealed that there were various ERs such as full-text, image, reference sources, and audio/visual. Similarly, the findings revealed that medical students have developed varying degrees of competences in the identifying and ac of accessing information on ERs. Also, there was a significant relationship between information literacy competence and ERs usage. The study concluded that respondents have demonstrated improved competences in information literacy. The study recommended that university management should ensure that information literacy programs cover the entire period of the study, so that the development of information literacy competence can be reinforced throughout the whole of medical education, not only on a few occasions like orientation period in the beginning of studies. In addition, university library management should organize more training to update students ' skills on information literacy as everything under digital are changing.